Augustine. Sense and imagination - Armstrong, A. H. (The Cambridge History of Later Greek and Early Medieval Philosophy, 1967)
Sense-knowledge, as Augustine always insists, is, like all knowledge, a work of the soul, not of the bodily organs; it is a work ‘of the soul by means of the body’. All his more sustained discussions of this type of knowledge are attempts to make comprehensible the way in which the mind uses the bodily organs of sense in obtaining knowledge from sense-experience. His treatment of sensation (sentire) is therefore in line with his view of man as a soul using a body, and the analogy of the craftsman using his tools is the model on which it is constructed. Thus he begins the long discussion of this topic in his De quantitate animae with the following definition: ‘sensation consists in the mind's awareness of the body's experience’. A necessary condition of sensation, according to this definition, is the encounter between the bodily sense-organ and the object perceived; but sensation is more than this physical encounter on which it depends, and involves the mind's awareness. The definition assimilates sensation to the category of passio or, more precisely, to an awareness by the mind of what the body ‘suffers’. Augustine deals at length with the difficulties of treating sensation in these terms. What, he asks, do the eyes ‘suffer’ in seeing something? Evodius, his interlocutor in the dialogue, invokes the analogy of feeling pain and emotions: what the eyes suffer when seeing is sight itself, just as a sick man suffers sickness or a rejoicing man joy.